Determinants of goodwill: Empirical study from emerging economies - Chelba, Ancuța-Anisia; Melega, Anatol; Grosu, Veronica (International Journal of Innovative Research and Scientific Studies, 2023)
Goodwill is increasingly receiving the interest of investors, auditors and other users of financial statements, therefore the need for comprehensive information on this topic has grown over time. The aim of this article is to analyze the determinants of goodwill in companies from emerging economy countries. The research is structured in two stages. The first stage of the research consists of a bibliometric analysis of the literature that is focused on the goodwill topic. The second part of the research consists in building an econometric model in order to assess the determinants of goodwill based on data reported by firms in emerging economy countries in 2021, namely the data reported by 21,977 companies from 100 emerging economy countries, structured into 94 industries. The obtained results are represented by the development of an econometric model that shows the implications of net profit, Economic Value Added (EVA), Earnings before Interest, Taxes, Depreciation and Amortization (EBITDA) and of research and development (R&D) expenses on goodwill fluctuations and vice versa. The results of our research highlight the fact that goodwill fluctuation is generated by the fluctuation of net profit, EVA, EBITDA and less by the R&D expenses. This study adds value to the literature by treating the subject differently, analyzing and evaluating the relationship between net profit, EVA, EBITDA, R&D expenses and goodwill.